2019 IEEE/CVF International Conference on Computer Vision (ICCV) 2019
DOI: 10.1109/iccv.2019.00627
|View full text |Cite
|
Sign up to set email alerts
|

FAMNet: Joint Learning of Feature, Affinity and Multi-Dimensional Assignment for Online Multiple Object Tracking

Abstract: Data association-based multiple object tracking (MOT) involves multiple separated modules processed or optimized differently, which results in complex method design and requires non-trivial tuning of parameters. In this paper, we present an end-to-end model, named FAMNet, where Feature extraction, Affinity estimation and Multi-dimensional assignment are refined in a single network. All layers in FAMNet are designed differentiable thus can be optimized jointly to learn the discriminative features and higher-ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(117 citation statements)
references
References 61 publications
0
115
0
2
Order By: Relevance
“…In the case of ruledistilled SiameseRF, a processing speed of approximately 1.3 Hz faster than the basic SiameseRF method was shown while maintaining the overall performance. For the MOT17 dataset, FAMNet [23] showed the fastest processing speed at 1.6 Hz among other three comparison methods. However, this method has a large speed difference of 10.8 Hz from the basic SiameseRF.…”
Section: Evaluation On Tracking Speedmentioning
confidence: 96%
See 3 more Smart Citations
“…In the case of ruledistilled SiameseRF, a processing speed of approximately 1.3 Hz faster than the basic SiameseRF method was shown while maintaining the overall performance. For the MOT17 dataset, FAMNet [23] showed the fastest processing speed at 1.6 Hz among other three comparison methods. However, this method has a large speed difference of 10.8 Hz from the basic SiameseRF.…”
Section: Evaluation On Tracking Speedmentioning
confidence: 96%
“…Tracking using a Siamese CNN for person reidentification in MOT has recently been studied [10][19]- [23]. A Siamese CNN applies the same network to the detection and tracker and calculates the similarity in the difference between output function values.…”
Section: Related Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the recent improvements in the MOT task involve fusing motion features with appearance one to better distinguish highly occluded objects and reidentify lost instances. The appearance clues usually come from convolutional neural networks [4,40]. However, Tang et al [35] showed that hand-crafted features, like the histogram of oriented gradients and colour histograms, might also be used if no training data is provided.…”
Section: Multi-object Trackingmentioning
confidence: 99%